2021
DOI: 10.1080/14992027.2021.1959953
|View full text |Cite
|
Sign up to set email alerts
|

Increased maximum power output may improve speech recognition with bone conduction hearing devices

Abstract: Objective: To investigate the influence of maximum power output of bone conduction hearing devices on speech recognition in quiet and in noise in experienced users of bone conduction hearing devices. Design: Prospective, randomised cross-over investigation comparing speech recognition performance, subjective sound quality, and device preference between two bone conduction hearing devices with different maximum power outputs. Study sample: Sixteen adult subjects with conductive or mixed hearing loss. Results: B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The results revealed that Baha 6 Max significantly outperformed Baha 5 under all test conditions. Related results have already been reported by Hua et al (9), Gawliczek et al (22), Bosman et al (23), and Hodgetts et al (24) and confirm the superior electroacoustic characteristics of Baha 6 Max. As shown by the audiometric thresholds results, the wider FR (up to 9700 Hz on the Baha 6 Max) and consequently the greater high-frequency gain were the determining factors for the superior performance of Baha 6 Max in noisy environments.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results revealed that Baha 6 Max significantly outperformed Baha 5 under all test conditions. Related results have already been reported by Hua et al (9), Gawliczek et al (22), Bosman et al (23), and Hodgetts et al (24) and confirm the superior electroacoustic characteristics of Baha 6 Max. As shown by the audiometric thresholds results, the wider FR (up to 9700 Hz on the Baha 6 Max) and consequently the greater high-frequency gain were the determining factors for the superior performance of Baha 6 Max in noisy environments.…”
Section: Discussionsupporting
confidence: 82%
“…A key factor to consider when selecting a BCHD for an individual is the gain that the device can provide, because the gain must be sufficient to amplify sounds above audiometric thresholds. Another crucial parameter for the selection process is the maximum power output (MPO), especially at a high frequency (9). MPO is defined as the strongest output level that a hearing device can provide and is an important parameter for selecting the best device for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…The effective dynamic range of EVS could further increase with a dedicated BC actuator designed for higher output in the low frequencies and direct coupling to the skull bone. Based on the results from previous studies 23 , 24 that showed improved speech perception with higher output power BC devices, this could result in even larger effect sizes with EVS vs E-only. However, it remains unclear how the findings from these studies showing the benefit of an increased broadband output would translate to higher low-frequency stimulation at the electro-vibrational cross-over frequency.…”
Section: Discussionmentioning
confidence: 96%
“…As the perception of the quality of the own voice may be important, a judgment of the quality of the own voice was included. We hypothesize that sound quality is optimal if the low-frequency output contributes to the sound perception ( Hua et al 2021 ) but at the same time is well below the MFO to avoid distortion.…”
Section: Introductionmentioning
confidence: 99%